1972
DOI: 10.1104/pp.49.5.769
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Reconstitution of Photosystem II

Abstract: Hill activity (oxygen evolution with ferricyanide as the electron acceptor), light-induced absorbance changes at liquid nitrogen temperature associated with the primary activity of photosystem II, and fluorescence yield changes at both low temperature and room temperature were measured with lyophilized spinach chloroplasts before and after extraction with hexane and reconstitution with p-carotene and plastoquinone A. Extraction eliminated the Hill activity, and both 8-carotene and plastoquinone A were required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

1972
1972
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 18 publications
3
24
0
Order By: Relevance
“…The fluorescence quenching imposed by DBMIB at low temperature is not relieved by irradiation. (The quenching by DBMIB is similar to that observed previously [8]with hexane extracted chloroplasts that had been reconstituted with plastoquinone A).…”
Section: Resultssupporting
confidence: 86%
“…The fluorescence quenching imposed by DBMIB at low temperature is not relieved by irradiation. (The quenching by DBMIB is similar to that observed previously [8]with hexane extracted chloroplasts that had been reconstituted with plastoquinone A).…”
Section: Resultssupporting
confidence: 86%
“…8) or a monomer (9) of chlorophyll (Chl), and the primary acceptor, Q, a special form of plastoquinone (PQ) (8)(9)(10)(11)(12)(13)(14). From measurements of nanosecond recombination luminescence from PS II, the lifetime of the state [P68OPheo] has been found to be z3 ns at 295 K [3].…”
mentioning
confidence: 99%
“…Instead of Vitamin K, Bishop (1959) found Q254 and showed that it restored activity. Later, Okayama and Butler (1972) showed, using hexane extraction, partial restoration by PQ and partial restoration by carotene. We found 50% restoration of ferricyanide and NADPH reduction with reduced PQ and less restoration with oxidized PQ (Wood and Crane 1965;Wood et al 1966).…”
Section: The Re-discovery Of the Plastoquinonementioning
confidence: 99%